Development of a Problem-Based Interactive E-Module with Social Emotional Learning in Tri Hita Karana to Enhance Mathematical Problem-Solving and Noble Character - Cahyaningrum, Kadek Ayu Kusuma; Ardana, I Made; Suweken, Gede (Darul Yasin Al Sys, 2025)
This study explores the development and effectiveness of an interactive e-module based on Problem-Based Learning (PBL) to enhance students' mathematical problem-solving skills and foster noble character traits. The e-module was designed for learning fractions and aimed to address the gap in traditional learning methods that lack student engagement and motivation. The research was conducted in two primary schools, SD Negeri 6 Panji and SD Negeri 1 Baktiseraga, involving 28 students. The results demonstrated significant improvements in students’ mathematical abilities, with average post-test scores increasing from 25.04 to 86.05 at SD Negeri 6 Panji and from 19.23 to 85.81 at SD Negeri 1 Baktiseraga. Moreover, the students showed positive behavioral changes, such as consistently greeting others and helping peers, reflecting the development of moral character. This study highlights the potential of interactive e-modules in enhancing both academic skills and character development.